Past and Present: Momentous Events that Shape the Indigenous Moroneno of Bombana District, Indonesia - Omar Pidani (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2017)
This research paper aims at providing a review of the literature and media coverage on the ethno-history of the Indigenous Moronene community. Thus far, there are less than a handful of sources on the ethno-linguistic identity and society that spread across the Rumbia Plain, Polea or Poleangcoastal regionand Kabaena Island in the District of Bombana, Indonesia. The review consists of the major events, which introduced external shocks to different parts of the Moronene society. It begins with the history of the ethnic settlement on the mainland of Southeast Celebes, locus of its ethno-linguistic relations with other ethnicgroups in Celebes and important ethnical structures and attributes. Furthermore, it continues with a description of the time line of major events that affect the society from the moment the country gained its independency in 1945 until the present time. We argue that ethnic and linguistic characteristics as well as these major events shape not only people’s collective actions and memory, but also their current identity, structure and patterns of social and environmental relationships. Linking this information into discussion of current social and development issues in the region is therefore a necessity.Keywords: Ethno-Linguistics, Indigenous, Moronene, Southeast Celebes